Ex vivo assay to evaluate the efficacy of drugs targeting sphingolipids in preventing SARS-CoV-2 infection of nasal epithelial cells - Becker, Katrin Anne; Carpinteiro, Alexander; Hoffmann, Markus; Pöhlmann, Stefan; Kornhuber, Johannes; Gulbins, Erich (STAR Protocols, 2021)
This protocol enables the testing of drugs against infection of epithelial cells with SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2), using pseudo-typed replication deficient vesicular stomatitis virus particles (pp-VSV) presenting the SARS-CoV-2 spike protein. After treating human volunteers with amitriptyline, an approved antidepressant and inhibitor of the acid sphingomyelinase, freshly isolated nasal epithelial cells were infected ex vivo and infection levels were quantified. This protocol offers the possibility to rapidly test the efficacy of potential drugs in the fight against COVID-19. For complete details on the use and execution of this protocol, please refer to Carpinteiro et al. (2020).
CRIS-Team Scopus Importer:2021-04-23
Keywords: Cell isolation; Cell-based assays